Mechanical behaviour of polymer based bamboo composite 1 - Izzat, Nazar (2016)
Polymer consist of the long chain molecules constructed of atoms (such as carbon and hydrogen) in the various arrangements with the different elements in the forming of basic building block of a polymer chain. Besides that, natural fiber reinforced polymer composite has a huge affinity to replace the composite made up of synthetic fiber. This is primarily because of the advantages like light weight, non-toxic, non-abrasive, easy availability, low cost and biodegradable properties. Bamboo fiber (BF) materials have attracted broad attention as reinforcement polymer composites due to their environmental sustainability, mechanical properties and recyclability and they can be compared with glass fiber. The main aim of this research was to study the feasibility of using a bamboo natural fiber as reinforcement in the development of partially biodegradable green and environmentally friendly composite. The reinforcement was bamboo fiber (BF) and the polymer matrix was polypropylene (PP). The composites were prepared by means of hot press with different weight percentages (20, 30 and 40). And then, the developed bamboo fiber (BF) reinforced polypropylene (PP) composites were then tested for their mechanical properties. On the basis of experimental results showed that the bamboo fibers (bundles) had a sufficient specific strength, which is equivalent to that of conventional glass fibers. The tensile strength and modulus of PP based composites using hot press, it is found that 20% of bamboo fiber mixed PP is giving optimum mechanical properties compare to 30% and 40%. But, there are also have some problem in process, which is need to consider in suitable extraction method, fiber length, resin application, moisture content and composite preparation techniques. From the experiments results, it can be concluded that using more bamboo fiber, the specimen become more brittle. Using “Video Measurement System”, it shows that the poor interfacial bonding generates partial spaces between the fiber and matrix material, hence resulting in a weak structure.